Stewardship Intervention to Optimize Central Venous Catheter Utilization in Critically Ill Children. Issue 2 (12th March 2021) - Blumenthal, Jennifer A.; Ormsby, Jennifer A.; Mirchandani, Dimple; Petti, Chonel A.; Carpenter, Jane; Geller, Maggie; Harding, Stephanie N.; O'Brien, Mary; Sandora, Thomas J.; Kleinman, Monica E.; Priebe, Gregory P.; Mehta, Nilesh M.
Abstract : Introduction: We aimed to describe utilization and indication(s) for long-term central venous catheters (CVCs) in a pediatric intensive care unit (PICU) and identify potential strategies to decrease CVC utilization. Methods: We conducted a single-center prospective quality improvement initiative at a 30-bed PICU in a large, freestanding, academic children's hospital. We created an electronic report to identify patients with an indwelling CVC for 7 days and older (defined as long term). We discussed the ongoing need for each long-term CVC with PICU clinicians at weekly interdisciplinary structured "CVC stewardship rounds." We then made recommendations around expedited removal of CVCs. We conducted multiple Plan-Do-Study-Act cycles to categorize CVC indications, identify modifiable factors, and educate PICU clinicians. We hypothesized that CVC stewardship rounds would decrease long-term CVC utilization in our PICU. Results: From October 2016 to September 2017, 607 long-term CVCs were eligible for the stewardship intervention. Compared to the preintervention period, we recorded a significant increase in peripherally inserted central catheters and a decrease in nontunneled CVCs ( P < 0.001). Most patients had single- or double-lumen CVCs in both the preintervention and intervention periods (86% and 91%, respectively). The utilization of overall long-term CVC devices, and those with modifiable indications, decreased during the intervention period. Conclusions: A single-center QI intervention focused on PICU CVC stewardship was associated with a decrease in CVC utilization.